Determinants of retirement planning behaviour among staffs in Panorama Melaka Sdn Bhd / Nurain Suhada Ismail - Ismail, Nurain Suhada (Faculty of Business and Management, 2015)
This research conducted focusing on the factors that influence retirement planning behaviour among staffs in Panorama Melaka Sdn Bhd. Retirement planning behaviour is very important to ensure that all working Malaysia citizen have the knowledge about the retirement. This topic was chosen because the researcher wants to know severely about perception and preparation of the employees towards their retirement planning. The determinants that involved in retirement planning behaviour are goal clarity, financial education, financial planning activities and social interaction. The respondents of this study were the staffs in Panorama Melaka Sdn Bhd which located in Melaka area. 100 questionnaires had been distributed among them. All 100 questionnaires managed to be collected and were analysed using SPSS Version 20.0. Multiple Regression method was used to find the best benefactor. Based on the findings, all the independent variables manage to have significant result towards the dependent variable which is retirement planning behaviour. However overall, the study suggest that goal clarity have the strongest influence on retirement planning behaviour with the highest Beta (0.527), followed by social interaction Beta (0.326). Next, it is closely followed by the financial planning activities Beta (0.288) and lastly financial education Beta (0.132).